1986
DOI: 10.1159/000215287
|View full text |Cite
|
Sign up to set email alerts
|

Low Molecular Weight Heparin Fraction PK10169: A New Therapeutic Means for Anticoagulant Therapy?

Abstract: To test the efficacy and safety of low molecular weight heparin (LMWH) fractions in thromboembolic diseases, 2 pilot studies were performed. The aim of the first was to test the antithrombotic efficacy of the LMWH PK 10169 (Pharmuka Laboratories) in 9 patients (group I) with acute pulmonary embolism documented by pulmonary angiography and scintiscan. The second study was intended to test the safety of the same LMWH fraction in a group (group II) of 30 patients at high risk of bleeding but also requiring antith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1987
1987
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…The interest in low molecular weight (LMW) heparin is constantly growing for several reasons, but particularly because they show a higher bioavailability [1], Clini cal trials suggest that some LMW heparins are as effective as heparin in postoperative thromboprophylaxis [4], Also, LMW hepa rins have been used in small groups of pa tients with well documented venous throm bosis or pulmonary embolism [3], Although laboratory monitoring is not compulsory in surgical patients receiving a conventional prophylactic regimen, it may be important in the last group of patients [3]. However, the activated partial thromboplas tin time (APTT) is only partially sensitive to LMW heparin, and no other easy routine test is available at this moment.…”
mentioning
confidence: 99%
“…The interest in low molecular weight (LMW) heparin is constantly growing for several reasons, but particularly because they show a higher bioavailability [1], Clini cal trials suggest that some LMW heparins are as effective as heparin in postoperative thromboprophylaxis [4], Also, LMW hepa rins have been used in small groups of pa tients with well documented venous throm bosis or pulmonary embolism [3], Although laboratory monitoring is not compulsory in surgical patients receiving a conventional prophylactic regimen, it may be important in the last group of patients [3]. However, the activated partial thromboplas tin time (APTT) is only partially sensitive to LMW heparin, and no other easy routine test is available at this moment.…”
mentioning
confidence: 99%
“…If no dose-limiting toxicity was identified in the first three patients, the dose was increased in controlled manner to 0.3 IU/cc in the next three patients and subsequently to 1.0 IU/cc, 3.0 IU/cc and 6.0 IU/cc to complete a clinical response curve. We chose our study dose range based on the well-studied therapeutic intravenous dosage [3] and the highest nontoxic dose of LMWH used in animal studies [4]. Additional surgeries were performed at the 3.0 IU/cc and 6.0 IU/cc dose levels in order to gain additional experience with the drug.…”
Section: Methodsmentioning
confidence: 99%
“…Iverson et al demonstrated that a LMWH (Fragmin, KabiVitrum AB, Stockholm) given at 5 IU/cc in the ocular irrigating solution markedly inhibited post-vitrectomy fibrin in a rabbit model without increasing intraocular hemorrhage [4]. Although no dose escalation study of intravitreal enoxaparin has ever been performed, a number of previous studies have determined the safe and effective intravenous dose of enoxaparin [3]. These studies have generally found an antithrombotic (anti-fibrinogenic) dose of enoxaparin at 0.1 to 0.2 IU/cc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the antithrom botic effect of various LMWH probably is not directly related to the anti Xa effect mea sured in the patient's plasma, this test princi ple is at present the most convenient [12]. Accordingly, LMWH therapy has mainly been monitored with factor-Xa-based chromogenic substrate (CS) assays [6,7,9,13,14], Preliminary data have suggested that the therapeutic range for some LMWH prepara tions is between 0.2 and 1.0 anti FXa U/ml [15].…”
Section: Introductionmentioning
confidence: 99%